2018
DOI: 10.1002/nop2.130
|View full text |Cite
|
Sign up to set email alerts
|

Course of maternal fatigue and its associated factors during the first 6 months postpartum: a prospective cohort study

Abstract: AimsTo identify the course of maternal fatigue during the first 6 months postpartum and to determine factors associated with it.DesignA prospective cohort study.MethodsWomen (N = 2,697) in 13 Japanese hospitals provided longitudinal data using self‐report questionnaires at five time points. Maternal fatigue was assessed using the Postnatal Accumulated Fatigue Scale. We focused on the effect of maternal age and parity on the course of maternal fatigue and used a mixed between/within‐subjects analysis of varianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
23

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 24 publications
2
36
0
23
Order By: Relevance
“…Women in this study may be overwhelmed with their family's needs, and in the case of refugee women with a large family and large number of children, lack of resources and support, and having a new child. It is no surprise that these responsibilities drain their energy and cause fatigue (Iwata et al, 2018;Schmied et al, 2017).This study suggested that participants' energy and fatigue, and health in general were negatively affected by the increased number of children in the family; this may, in part, lead to increased financial burden. However, with increasing age and length of marriage, women usually develop better adaptation to the increased demands of the family.…”
Section: Discussionmentioning
confidence: 84%
“…Women in this study may be overwhelmed with their family's needs, and in the case of refugee women with a large family and large number of children, lack of resources and support, and having a new child. It is no surprise that these responsibilities drain their energy and cause fatigue (Iwata et al, 2018;Schmied et al, 2017).This study suggested that participants' energy and fatigue, and health in general were negatively affected by the increased number of children in the family; this may, in part, lead to increased financial burden. However, with increasing age and length of marriage, women usually develop better adaptation to the increased demands of the family.…”
Section: Discussionmentioning
confidence: 84%
“…This study also shows that primipara, but not multipara women, without functional support received more support from multidisciplinary agencies than those with functional support from their biological maternal grandmothers. A recent prospective cohort study demonstrated that primiparas suffer from a higher level of fatigue compared to multiparas shortly after delivery 20. Another survey of the perinatal mother–daughter relationship showed that more primiparas require their mothers’ perinatal help more relative to multipara women as parity is associated with the practical presence of grandmother perinatal support 4.…”
Section: Discussionmentioning
confidence: 99%
“…It is a critical period in life and will have a great impact on maternal health. [1][2][3] After childbirth, many women have some psychosocial problems, such as fatigue, 4 anxiety, 5 and depression. 6 The study of postpartum fatigue is particularly critical: on the one hand, postpartum fatigue is one of the common symptoms after childbirth.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, postpartum fatigue is not easy to detect and is often ignored by many people. 4 Around the 1990s, foreign scholars began research on postpartum fatigue. At present, there are many studies on postpartum fatigue in foreign countries, and relatively few in China.…”
Section: Introductionmentioning
confidence: 99%